Pattern and causes of the establishment of the invasive bacterial potato pathogen Dickeya solani and of the maintenance of the resident pathogen D. dianthicola - Blin, Pauline (Blackwell Publishing, 2021)
Invasive pathogens can be a threat when they affect human health, food production or ecosystem services, by displacing resident species, and we need to understand the cause of their establishment. We studied the patterns and causes of the establishment of the pathogen Dickeya solani that recently invaded potato agrosystems in Europe by assessing its invasion dynamics and its competitive ability against the closely related resident D. dianthicola species. Epidemiological records over one decade in France revealed the establishment of D. solani and the maintenance of the resident D. dianthicola in potato fields exhibiting blackleg symptoms. Using experimentations, we showed that D. dianthicola caused a higher symptom incidence on aerial parts of potato plants than D. solani, while D. solani was more aggressive on tubers (i.e. with more severe symptoms). In co-infection assays, D. dianthicola outcompeted D. solani in aerial parts, while the two species co-existed in tubers. A comparison of 76 D. solani genomes (56 of which have been sequenced here) revealed balanced frequencies of two previously uncharacterized alleles, VfmB(Pro) and VfmB(Ser), at the vfmB virulence gene. Experimental inoculations showed that the VfmB(Ser) population was more aggressive on tubers, while the VfmB(Pro) population outcompeted the VfmB(Ser) population in stem lesions, suggesting an important role of the vfmB virulence gene in the ecology of the pathogens. This study thus brings novel insights allowing a better understanding of the pattern and causes of the D.solani invasion into potato production agrosystems, and the reasons why the endemic D. dianthicola nevertheless persisted.